Wealth status and sexual partnership pattern among Nigerian men (2014)
Studies in sub-Saharan Africa have shown that many people engage in multiple sexual partnerships despite the high knowledge about the contribution of such practice to the spread of HIV. The culture in many African countries especially in Nigeria favour men to engage in sexual experimentation with many sexual partners as a symbol of manhood. Past studies on sexual behaviour in Nigeria have focused on women and adolescents while men’s sexuality has received less attention. This study used data extracted from 2007 National HIV/AIDS and Reproductive Health Survey of sexually active Nigerians to investigate correlates and pattern of multiple sexual partnerships among men in Nigeria using multilevel logistic regression models. The findings indicate that individual characteristics such as ever use of condom influenced sexual behaviour of men compared to their contextual characteristics. Compared to men in the poorest group, moderately rich men were more likely to have multiple (OR=1.10, 95%CI=0.93-1.30) and non-regular sexual partners (OR=1.05, 95%CI=0.89-1.25). We found marital status, ever use condom, students, age (21-49years) as significant determinants of multiple sexual partnerships. Sexual behaviour in the men population is driven not only by their occupations or economic state; younger men are more prone to risky sexual behaviour.